2023
DOI: 10.1001/jamanetworkopen.2022.48685
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Machine Learning Model for Sonographic Assessment of Gestational Age

Abstract: ImportanceFetal ultrasonography is essential for confirmation of gestational age (GA), and accurate GA assessment is important for providing appropriate care throughout pregnancy and for identifying complications, including fetal growth disorders. Derivation of GA from manual fetal biometry measurements (ie, head, abdomen, and femur) is operator dependent and time-consuming.ObjectiveTo develop artificial intelligence (AI) models to estimate GA with higher accuracy and reliability, leveraging standard biometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The estimation of GA is one of the important indications for obstetric US in early pregnancy that helps to adjust maternity care and identify complications such as prematurity or fetal growth disorders [144]. It is usually calculated using the last menstrual period and is confirmed with fetal CRL and biometry.…”
Section: Prediction Of Gestational Agementioning
confidence: 99%
See 2 more Smart Citations
“…The estimation of GA is one of the important indications for obstetric US in early pregnancy that helps to adjust maternity care and identify complications such as prematurity or fetal growth disorders [144]. It is usually calculated using the last menstrual period and is confirmed with fetal CRL and biometry.…”
Section: Prediction Of Gestational Agementioning
confidence: 99%
“…Lastly, four studies used data from the Fetal Age Machine Learning Initiative (FAMLI), which is an obstetrical US development project in low-income settings. The purpose of these studies, which were based on US data from the US and Zambia, was the successful establishment of an AI algorithm for GA estimation from simplified blind US sweeps of US novices in low-resource countries [144,145,152,153]. The benefits of the GA AI models were the possibility for application in low-resource countries [144,145,148,149,152], even without internet connectivity [145], and in portable devices [148], promising high accuracy with an error of 3.9 to 5 days in GA estimation [149,152].…”
Section: Prediction Of Gestational Agementioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound measurement of placental thickness is a simple and effective criterion for determining GA. The diameter around the head, biparietal diameter, abdominal circumference, and femoral length are all sonographically derived fetal characteristics that are used to date the pregnancy 8,9 . These are commonly used to estimate GA, either alone or in combination.…”
Section: Introductionmentioning
confidence: 99%
“…The diameter around the head, biparietal diameter, abdominal circumference, and femoral length are all sonographically derived fetal characteristics that are used to date the pregnancy. 8,9 These are commonly used to estimate GA, either alone or in combination. Researchers have demonstrated that placental markers effectively assess children for GA (GA) and that intrauterine growth restriction (IUGR) requires early intervention.…”
Section: Introductionmentioning
confidence: 99%